1975
DOI: 10.3181/00379727-148-38578
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical and Morphologic Dimensions of Human Hepatitis A Virus Strain CR326

Abstract: A previous report ( I ) from these laboratories described the recovery in S. mystax marmosets of CR326 and related strains of human hepatitis A virus from cases of hepatitis A that occurred in Costa Rica. The etiologic relationship of the CR326 virus to hepatitis in man was established based on the demonstration of physical-chemical properties considered characteristic of human hepatitis A virus (viz., small size and heat, ether and acid stability) (2), and on the development in patients with hepatitis A of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
2
3

Year Published

1976
1976
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(48 citation statements)
references
References 2 publications
1
42
2
3
Order By: Relevance
“…This observation contrasts with those of Feinstone et al (1973) and Provost et al (1975), who found 27-nm particles associated with hepatitis A. However, Thornton, Zuckerman and Almeida (1975) have recently described particles of variable diameter in faeces from a chimpanzee infected with MS-1 agent; their particles ranged in size from 24 to 29 nm.…”
Section: Discussioncontrasting
confidence: 55%
“…This observation contrasts with those of Feinstone et al (1973) and Provost et al (1975), who found 27-nm particles associated with hepatitis A. However, Thornton, Zuckerman and Almeida (1975) have recently described particles of variable diameter in faeces from a chimpanzee infected with MS-1 agent; their particles ranged in size from 24 to 29 nm.…”
Section: Discussioncontrasting
confidence: 55%
“…In agreement with Provost et al (1975) we assume that the lower density value for HAV represents an association with lipids. , however, reported contradictory data: after extraction with chloroform, the buoyant density of light HAV particles (1.27 g/ml) propagated in BS-C-1 cells was unchanged.…”
mentioning
confidence: 65%
“…These results suggest that HEV virions in serum possess the ORF3 protein on their surfaces, in association with lipids, similar to those in the supernatant of cultured cells (63), and would reconcile the apparently contradictory observation that IgM and IgA antibodies, which are capable of viral neutralization, and infectious virus coexist in acute-phase serum specimens, as reported for hepatitis A virus (HAV) (19,35). Provost et al (34) reported that the infectious HAV present in acute-phase marmoset sera banded at two densities in CsCl (1.34 g/ml and 1.15 g/ml), suggesting that the less-dense particles represent lipid-associated virions. A similar banding pattern was observed by Lemon and Binn (20), who reported that the HAV released from infected BS-C-1 cells was incompletely neutralized when it was incubated with a variety of convalescent-phase sera (nonneutralizable fraction of 17 to 32%) and that chloroform extraction of virus resulted in a substantial reduction of the nonneutralizable fraction (to Ͻ1%).…”
Section: Discussionmentioning
confidence: 99%
“…Although lipid-associated virions of other nonenveloped viruses, such as HAV, have been reported (20,34,37), the underlying mechanism by which HEV particles in the circulation can be propagated in cultured cells, similar to those in culture supernatant, despite the fact that they are seemingly "enveloped" and nonneutralizable by immune sera, needs to be clarified in future studies.…”
Section: Discussionmentioning
confidence: 99%